Factors Influencing Demotivation to Learn Arabic Among Students of Arabic Language Education Program - Susiawati, Wati (Arabi : Journal of Arabic Studies, 2024)
The study of motivation typically examines the reasons behind an individual's actions or behaviors, with a focus on identifying factors that either hinder or enhance enthusiasm for learning. This research aims to uncover commonalities in the challenges faced by students to propose a more effective and efficient learning process. The study sample consists of first and third-semester students enrolled in the Arabic Language Education program at UIN Jakarta during the 2021/2022 academic year. Data were collected using a questionnaire distributed to students and through direct observations of the learning process. Findings indicate that intrinsic factors, particularly self-confidence, play a crucial role in motivating students to learn a second language. Despite facing various challenges, students demonstrated resilience and a continued effort to maintain their motivation in learning Arabic. This research highlights the importance of fostering self-confidence and addressing demotivating factors to enhance the overall learning experience.